Pengembangan Model Permainan King Queen Pembelajaran Senam Lantai Peserta Didik Sekolah Dasar - Naila Elmuna; Agus Darmawan; Ranu Baskora Aji Putra; Dwi Tiga Putri (Universitas Negeri Semarang, 2024)
This present research used research and development (R & D) research methods, the subjects in this research are fourth grade in Elementary School. Data collection was carried out using expert evaluation sheets, student questionnaire sheets, and observation sheets. This finding showed that data analysis and evaluation results from experts with an average of 90% including the